If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(f + -1) = -49 Reorder the terms: 7(-1 + f) = -49 (-1 * 7 + f * 7) = -49 (-7 + 7f) = -49 Solving -7 + 7f = -49 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 7f = -49 + 7 Combine like terms: -7 + 7 = 0 0 + 7f = -49 + 7 7f = -49 + 7 Combine like terms: -49 + 7 = -42 7f = -42 Divide each side by '7'. f = -6 Simplifying f = -6
| 2w+2(w+12)=44 | | 90=10(m+3) | | 7y+3=94 | | -3=3(j+16) | | 3(x-7)+2=4x+4 | | 17p-6=3(8p+5) | | 19x-63=112+14x | | 3(n+19)=12 | | 5x^4+24x^2+19=0 | | -3(q+24)=63 | | 32+3c=80 | | Z=1813/(2*i²) | | q-82/7=2 | | 2/r=t/-4t-6 | | 19=-3.5x^2+14x+3 | | -62+21=12n-15 | | -3.6w-4.2w= | | -2(w-8)+6=-12 | | 5x-(4x+3)=8 | | 14x+21=-19 | | 3-1=2-1+1 | | (lgn-lgx)*(n-lgx)=0 | | 8a-2=6 | | -2(f-57)=14 | | -3(y-6)=-6 | | 7+cx=10 | | 12d-8=-20 | | 10=9+1 | | 40(.9-.8)=5x | | 6(z+2)=90 | | -23x-13=27 | | 18-t=9 |